Digitization of the car: Impact on automotive logistics - Daniel Fruhner; Katja Klingebiel (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The digitization of the car is advancing in the four prominent areas called CASE (Connected, Autonomous, Shared & Services, Electric). The respective changes to the product structure will further increase the complexity of automotive logistics. This paper has methodologically clustered these changes and identified the impacts on logistics. Methodology: Via a systematic literature analysis, the automotive product structure has been categorized into six main clusters and subclusters. Subsequently, the anticipated changes in the product structure triggered by digitalization have been classified. In the last step, the resulting impacts and necessary developments for logistics have been deduced. Findings: In the course of the digitization of the car, only very few systems and modules remain unchanged. Adaptations in the product structure can be expected to accelerate in the future. Conceptual solutions for automotive logistics are necessary. First approaches, as well as remaining gaps, have been identified. Originality: Digitalization and technological trends pose new challenges on logistics not yet met by scientific literature, though practice offers first conceptual ideas. This paper is the first to methodologically and holistically identify the implications of the digitalization of the car on logistics, thus providing the basis for assessing conceptional solutions.
urn:nbn:de:gbv:830-882.0161784; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; innovation management; technology management